Impact of Child Sexual Abuse on Educational Pathways of Children in Sri Lankan Tea Plantations - N. M. P. K. Kumari; L. N. P. Wedikandage (Indonesian Scientific Publication, 2026)
Child sexual abuse (CSA) and its secondary consequences significantly threaten educational participation in Sri Lanka’s plantation sector. This research explores how these risks disrupt the education of children in marginalized communities, specifically focusing on the